2014
DOI: 10.1111/jan.12490
|View full text |Cite
|
Sign up to set email alerts
|

A companionship between strangers – learning from fellow people with cancer in oncology wards

Abstract: Learning from exchanges of experiences with fellow patients provided a better understanding about the disease and was valued because it was first-hand knowledge. Patients' personal experience of disease is an underused resource in nursing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…They also find, as in our study, that patients might feel the relationship being forced on them. Contrary, Andersen, Larsen, and Birkelund () finds that fellow patients can provide a better understanding of the disease, but also, that there is a need for the healthcare professionals to be aware of the relationships between fellow patients—between strangers with common disease.…”
Section: Discussionmentioning
confidence: 99%
“…They also find, as in our study, that patients might feel the relationship being forced on them. Contrary, Andersen, Larsen, and Birkelund () finds that fellow patients can provide a better understanding of the disease, but also, that there is a need for the healthcare professionals to be aware of the relationships between fellow patients—between strangers with common disease.…”
Section: Discussionmentioning
confidence: 99%
“…In a range of studies (34 of 45), the participant's perspective constituted the argument for the relevance of the ethnographic method and was explicit in study aims, that is Bergenholtz et al who wrote: ‘… to describe and understand cultures by grasping the insiders’ (the natives’ and participants’) point of view’ (p. 2259), and Andersen et al who set their objective to: ‘…understand another way of life from the point of view of the people concerned’.(p. 271), and in Danbjørg et al where the authors sat the purpose of the observations to: ‘get a grasp of the problem in the local setting’ (p. 726).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated in other research that some patients may choose not to join a supportive group‐based intervention because it may serve as a reminder of their own vulnerability (Guenther, Stiles, & Champion, ). Research has also reported that exchanging emotional thoughts while interacting in a dynamic tension between being close and maintaining a distance between strangers with a common disease may be a challenge (Album, ; Andersen et al, ; Borregaard & Ludvigsen, ). In the present study, the community of doing exercise in the group seemed to meet the challenges of discomfort in the relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated how patient–patient interaction in general might be an important part of the social support system during hospitalisation and how a companionship between strangers may emerge. However, it is also reported how the relationship might be ambiguous (Andersen, Larsen, & Birkelund, ; Birkelund & Larsen, ; Borregaard & Ludvigsen, ; Larsen, Larsen, & Birkelund, ). Studies on exercise for patients with cancer have also reported social benefits of participating in group‐based interventions (Adamsen, Andersen, Lillelund, Bloomquist, & Moller, ; Backman, Browall, Sundberg, & Wengstrom, ; Missel et al, b); however, the meaning of participating in group‐based exercise for patients after lung cancer surgery is sparsely investigated.…”
Section: Introductionmentioning
confidence: 99%